BRIDGING GENDER GAPS IN EDUCATION THROUGH ISLAMIC VALUES AND TECHNOLOGY AT PPTQ AL-HASAN - Syahrudin, Syahrudin; Aisi, Okta Khusna; Susanto, Roni; Isa, Khairunesa (EGALITA, 2025)
Abstract Achieving gender equality in education remains a pressing global challenge and a core component of the Sustainable Development Goals (SDGs), particularly in regions where religious values deeply influence social structures. This study explores an integrative approach that combines Islamic principles with educational technology to address gender disparities in education, with a focus on Madrasah Riyadlatusy Syubban, part of Pondok Pesantren Tahfidzul Qur’an Al-Hasan in Ponorogo, East Java. Utilizing a qualitative case study design, the research investigates how Islamic values that uphold gender justice can be harmonized with technological innovations to expand access to education and enhance learning outcomes. Data were gathered through in-depth interviews, participant observation, and institutional document analysis. The findings reveal that aligning Islamic teachings on gender justice with the use of digital platforms and online applications significantly improves educational access for female students, while also fostering their intellectual and technical growth. This synergy not only narrows the gender gap in religious education but also supports broader efforts toward women's empowerment in a culturally resonant manner. The study contributes to both theoretical and practical discourses by proposing a sustainable and inclusive educational model that integrates faith-based values with digital innovation. It offers a contextual framework for promoting gender equality in Islamic educational settings, and highlights the potential of religious institutions to play a transformative role in achieving the SDGs, especially in advancing quality education and empowering women.  Keywords: Gender Equality; Inclusive Education; Educational Technology; Islamic Values; SDGs; Madrasah; Women's Empowerment; Value Integration.Abstrak Mewujudkan kesetaraan gender dalam pendidikan tetap menjadi tantangan global yang mendesak serta merupakan salah satu komponen utama dalam Tujuan Pembangunan Berkelanjutan (SDGs), khususnya di wilayah yang struktur sosialnya sangat dipengaruhi oleh nilai-nilai keagamaan. Studi ini mengeksplorasi pendekatan integratif yang menggabungkan prinsip-prinsip Islam dengan teknologi pendidikan untuk mengatasi kesenjangan gender dalam sektor pendidikan, dengan fokus pada Madrasah Riyadlatusy Syubban yang merupakan bagian dari Pondok Pesantren Tahfidzul Qur’an Al-Hasan di Ponorogo, Jawa Timur. Menggunakan desain studi kasus kualitatif, penelitian ini menelaah bagaimana nilai-nilai Islam yang menjunjung keadilan gender dapat diselaraskan dengan inovasi teknologi untuk memperluas akses pendidikan dan meningkatkan kualitas pembelajaran. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan analisis dokumen institusional. Hasil penelitian menunjukkan bahwa penyelarasan antara ajaran Islam tentang keadilan gender dan pemanfaatan platform digital serta aplikasi daring secara signifikan meningkatkan akses pendidikan bagi santri perempuan, sekaligus mendorong pertumbuhan intelektual dan keterampilan teknis mereka. Sinergi ini tidak hanya mempersempit kesenjangan gender dalam pendidikan keagamaan, tetapi juga mendukung pemberdayaan perempuan secara lebih luas dalam konteks budaya yang relevan. Studi ini memberikan kontribusi terhadap wacana teoritis dan praktis dengan mengusulkan model pendidikan berkelanjutan dan inklusif yang mengintegrasikan nilai-nilai keagamaan dengan inovasi digital. Penelitian ini juga menawarkan kerangka kontekstual dalam mendorong kesetaraan gender di lingkungan pendidikan Islam, serta menyoroti potensi lembaga keagamaan untuk memainkan peran transformatif dalam pencapaian SDGs, khususnya dalam meningkatkan mutu pendidikan dan pemberdayaan perempuan.  Kata Kunci: Kesetaraan Gender; Pendidikan Inklusif; Teknologi Pendidikan; Nilai Islam; SDGs; Madrasah; Pemberdayaan Perempuan; Integrasi Nilai